Mathematical Modeling of Microwave Drying Kinetics of Ginger (Zingiber officinale) Slices - Kumar, Ashok; Kulkarni, Neha; Kedarnath (Journal of Postharvest Technology, 2014)
In this work, the microwave drying behaviour of ginger was investigated. The constant rate period is absent from the drying curves. The drying process took place in the falling rate period. The drying data were fitted to five mathematical models namely, Exponential, Page, Henderson and Pabis, Logarithmic and Power law models and validated on the basis of determination of coefficient (R2), reduced mean square (χ2) of the deviation, mean bias error (EMB) and root mean square error (ERMS) between the observed and predicted values of moisture ratios. Page model was found to fit best, representing an excellent tool for estimation of the drying time and the values of R2, χ², ERMS and EMB were in the ranged of 0.995 to 0.997; 0.0006 to 0.005; 0.022 to 0.038 and 0.005 to 0.009 respectively. The effective diffusivity coefficient of moisture transfer from ginger was found within the range of 2.5356 × 10-11 to 1.2678 × 10-9 m2 s-1.